Forest Dynamics of Peat Swamp Forest in Sebangau, Central Kalimantan - EDI MIRMANTO (Biodiversitas Journal of Biological Diversity, 2009)
plots. The plots were set up in natural peat swamp forest in the upper catchments of Sebangau, Central Kalimantan. Aim of the study is to understand the dynamics and vegetation changes of forest studied during period of study. The peat swamp forest in the study site might be categorized as moderately forest dynamic in term of rate of growth, mortality and recruitment. Annual relative growth rate and mortality rate was comparable to previous study but recruitment rate relatively higher. There was significant effect of diameter class on annual growth rate, but not to mortality rate. Even not too strong two environment factors (peat depth and distance to river) were significant correlated with rate of mortality and recruitment. During two-year period study there was no significant changes in vegetation structure.Key words: Central Kalimantan, dynamic, growth, mortality, peat swamp forest, recruitment, Sebangau.